2019
DOI: 10.1038/s41598-019-42383-8
|View full text |Cite
|
Sign up to set email alerts
|

Satellitome landscape analysis of Megaleporinus macrocephalus (Teleostei, Anostomidae) reveals intense accumulation of satellite sequences on the heteromorphic sex chromosome

Abstract: The accumulation of repetitive DNA sequences on the sex-limited W or Y chromosomes is a well-known process that is likely triggered by the suppression of recombination between the sex chromosomes, which leads to major differences in their sizes and genetic content. Here, we report an analysis conducted on the satellitome of Megaleporinus macrocephalus that focuses specifically on the satDNAs that have been shown to have higher abundances in females and are putatively located on the W chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 43 publications
5
54
0
Order By: Relevance
“…In the fish Megaleporinus microcephalus, 164 satDNA families have been isolated, which is, by far, the most satellite-rich species discovered to date. Nevertheless, the satDNA of M. macrocephalus only represented 13.47% (female) and 11.99% (male) of the genome [61]. Therefore, the existence of multiple satDNA families seems to be a common characteristic of eukaryotic genomes as they have also been found in plants and vertebrates [61][62][63].…”
Section: Resultsmentioning
confidence: 99%
“…In the fish Megaleporinus microcephalus, 164 satDNA families have been isolated, which is, by far, the most satellite-rich species discovered to date. Nevertheless, the satDNA of M. macrocephalus only represented 13.47% (female) and 11.99% (male) of the genome [61]. Therefore, the existence of multiple satDNA families seems to be a common characteristic of eukaryotic genomes as they have also been found in plants and vertebrates [61][62][63].…”
Section: Resultsmentioning
confidence: 99%
“…The high A+T content could be a consequence of satDNA being subject to epigenetic modifications such as the methylation of cytosines, consequently deamination of 5-methylcytosines forming more AT base pairs in P. leptodactylus satDNAs. In the fish Megaleporinus microcephalus short (<100 bp) and long (>100 bp) satellites had a similar amount of A+T content (Utsunomia et al, 2019 ). In the fern V. speciosa satDNAs longer unit length showed a higher A+T content (Ruiz-Ruano et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found great diversity of satDNA repeats in the genome of P. leptodactylus with a total of 258 satellite families which is by far the most satellite-rich species discovered to date. A large number of different satDNA elements is found in other organisms such as the fish Megaleporinus macrocephalus (Teleostei, Anostomidae) where 164 satellite repeats have been described (Utsunomia et al, 2019 ). Similar to P. leptodactylus , in M. macrocephalus , short satellites dominate in the genome.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, high-throughput sequencing contributed significantly to increase our knowledge regarding satDNA sequences [63]. Next generation sequencing (NGS; e.g., Illumina), allied to newly developed bioinformatics tools capable of identifying satDNA sequences in unassembled data (e.g., RepeatExplorer) [64][65][66], helped uncover the extent of satDNAs present in the genome of different species, revealing unpredicted levels of satDNA diversity (e.g., [34,[67][68][69][70][71]). For instances, 62 satDNA families were identified in the genome of the migratory locust, leading to the coining of the term 'satellitome' to refer to the whole collection of satDNA families found in a single genome [34], a part of the 'repeatome', a term proposed previously [33] to refer to the collection of all repetitive sequences in a genome (TEs, satDNAs, etc.).…”
Section: Satdna Features and Organization In The Genome And Chromosommentioning
confidence: 99%
“…For instances, 62 satDNA families were identified in the genome of the migratory locust, leading to the coining of the term 'satellitome' to refer to the whole collection of satDNA families found in a single genome [34], a part of the 'repeatome', a term proposed previously [33] to refer to the collection of all repetitive sequences in a genome (TEs, satDNAs, etc.). This number has been surpassed by a recent study where 164 satDNA families have been identified in Teleostei fish, being this the biggest satellitome characterized for a given species so far [70]. The availability of a methodology capable of assessing satDNA array abundance and diversity led to an explosion of comparative studies across a wide range of clades, including mammals, insects and plants (e.g., [44,45,69,[71][72][73]) providing insights into these sequences.…”
Section: Satdna Features and Organization In The Genome And Chromosommentioning
confidence: 99%